AN OVERVIEW INSULIN USED IN OUTPATIENT WITH DIABETES MELLITUS TYPE 2 AT HIDAYATULLAH ISLAMIC YOGYAKARTA HOSPITAL - Kartika Nur Fahmi; Qarriy 'Aina Urfiyya (Universitas Kadiri, 2022)
Diabetes Mellitus (DM) has a high prevalence and can become a public health problem. The Province of the Special Region of Yogyakarta is included in the top three ranks with DM cases at the age of 15 years, namely 3.1%. The purpose of this study was to determine patient characteristics and descriptions of insulin use in outpatient BPJS patients at Hidayatullah Islamic Hospital Yogyakarta for the period October - December 2021. This study used a descriptive observational design, with retrospective data collection on the medical records of type 2 DM patients BPJS outpatients. This study used purposive sampling technique, a total of 93 medical records. Descriptive data analysis on patient characteristics and insulin use. The result of this study was DM type 2 BPJS outpatients with the highest patient age category was <60 years (53.80%), the highest gender was female (57%), and highest comorbidities was hypertension (68%). The largest therapeutic use was insulin monotherapy (53.76%), with insulin novorapid (74%).